Kinetic Analysis of the Amino Terminal End of Active Site Loop of Lactate Deyhdrogenase from Plasmodium Vivax - MUTLU, ÖZAL (GALENOS YAYINCILIK, 2012)
Objective: In this study, kinetic analysis was performed to understand the functional importance of the amino terminal of the active site of previously mutated Plasmodium vivax Lactate Dehydrogenase enzyme by mimicking Toxoplasma gondii I, II, Eimeria acervulina and Eimeria tenella LDH's. Material and Methods: Mutant LDH genes were amplified by PCR and 6xHistag was added to the C-terminal of the enzymes. Then LDH enzymes are overproduced as recombinant in E. coli cells, purified by Ni-NTA agarose matrix and kinetic properties were analysed. Results: Observing increase of K-m values of mutant enzymes showed that mutations in this place caused decreasing affinity of enzyme for its substrate. However k(cat) values were about the same throughout all mutant proteins. Conclusion: Sensitivity of the studied region emphasizes the significance of this site for drug design studies for both Plasmodium and some other Apicomplexans.
Keywords: Lactate dehydrogenase; Plasmodium vivax; antimalarial drug; site-directed mutagenesis; kinetic analysis; DEHYDROGENASE GENE; FALCIPARUM; EXPRESSION; PARASITE; MALARIA; CLONING